THERMODYNAMIC ANALYSIS OF SOLAR HEAT PUMP ASSISTED HEATING SYSTEMS - Siyahhan Turkgenc, Zozan; Cebi, Alican; Celen, Ali; Dalkilic, Ahmet Selim; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2014)
In this study, a system has been developed which can be used for heating buildings by utilizing solar energy, which is free and abundant in our country, with the aim of minimizing fossil based fuel consumption especially at wintertime and this system's efficiency has been analyzed mathematically with numerical methods. First of all, in this study the performance of a solar heat pump system is examined. The city of Antalya is chosen for this study which is in the southern region of Turkey with an abundant source of solar energy. The usability of solar energy throughout the year is examined and its application areas in building heating with the utilization of heat pumps are determined. In addition an auxiliary system with an alternative energy source is considered in case solar energy is insufficient by itself. In order to determine all of the above, energy analysis of the system is performed. The advantages of the solar heat pump heating system are studied considering the amount of energy saved and the efficiency of the system. Thermodynamic and thermoeconomic analysis has been carried out in order to determine how effectively the solar energy is utilized by the system and the advantages of solar heat pump.
Keywords: UNDERGROUND SEASONAL STORAGE; ECONOMICAL ANALYSIS; PERFORMANCE; PLANTS; Engineering